2007
DOI: 10.1111/j.1365-2249.2007.03335.x
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate induces poly(ADP-ribose) polymerase-dependent, caspase 3-independent apoptosis in subsets of proliferating CD4+ T cells

Abstract: SummaryThe mechanism of action of methotrexate (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Although PARP represents a main cleavage target of caspases, 44 alternative pathways may activate PARP as reported in T lymphocytes treated with methotrexate, lung cancer cells transduced for MBP-1, and breast cancer cells treated with PI3K/mTOR inhibitor. [45][46][47][48] Here, we show that IL-23 exerted also antiproliferative effects on B-ALL cells that may be ascribed to 2 different mechanisms. First, we demonstrated that IL-23 treatment damped in vivo expression of cyclin D1, another target of miR15a, 49 whose functions are directly associated with cancer progression and invasion.…”
Section: Discussionmentioning
confidence: 65%
“…Although PARP represents a main cleavage target of caspases, 44 alternative pathways may activate PARP as reported in T lymphocytes treated with methotrexate, lung cancer cells transduced for MBP-1, and breast cancer cells treated with PI3K/mTOR inhibitor. [45][46][47][48] Here, we show that IL-23 exerted also antiproliferative effects on B-ALL cells that may be ascribed to 2 different mechanisms. First, we demonstrated that IL-23 treatment damped in vivo expression of cyclin D1, another target of miR15a, 49 whose functions are directly associated with cancer progression and invasion.…”
Section: Discussionmentioning
confidence: 65%
“…Ciclosporin A and tacrolimus bind to speci fic intra cellular receptors (immunophilins) and act by blocking the activation of the transcription factor nuclear fac tor of activated T cells (NFAT) that controls cytokine gene transcription and apoptosis resistance of lympho cytes 18,19 . Moreover, methotrexate affects survival of immune cells by blocking cell proliferation and indu cing apoptosis 20 . This drug also increases endogenous adeno sine release, alters expression of cellular adhesion mol ecules and suppresses production of proinflammatory cytokines 21 .…”
Section: Classic Immunosuppressive Drugsmentioning
confidence: 99%
“…Other studies showed the pro-apoptotic action of DMARDS (non-biologicals) such as sulfasalazine,57 and hydroxichloroquine 58. Methotrexate, which in many cases is used in conjunction with TNF-α antagonists, and cyclophosphamide also promote cellular apoptosis in activated T CD4 and CD8 cells, but not in resting cells, through CD95 sensitivity 59,60…”
Section: Tnf-α Antagonists and Apoptosismentioning
confidence: 99%